Online assessment in higher education during Spanish confinement by COVID-19: The view of students - Díez-Gutiérrez, Enrique; Gajardo Espinoza, Katherine (Journal of University Teaching and Learning Practice, 2021)
The purpose of this study is to describe how university students rate the evaluation systems and strategies that have been proposed for use in Higher Education during the period of COVID-19 confinement and online teaching as a result of the coronavirus crisis in Spain. For this purpose, we prepared a descriptive study by means of an online questionnaire, specifically designed on the basis of evaluation and qualification proposals made by REACU (Spain), ANECA (Spain), UNESCO, and the Spanish Ministry of Universities. The results obtained, after applying them to a sample of 1008 students from different universities in Spain, and covering most of the Autonomous Communities (17), indicate that students agree with and value the changes recommended by agencies and agree that the assessment should be flexible, diverse, formative and continuous. On the other hand, their experiences indicate that the Universities have not yet applied some of the suggested recommendations.